National Economy and Macroeconomics - Yulduz Pirnazarovna Urinbaeva (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
The article considers the content of national and macroeconomics, their differences, types and indicators. It develops definitions of the concepts of national economy and macroeconomics, types of national economy on six indicators, macroeconomic indicators and ways to determine them, as well as their interrelationships.